2010
DOI: 10.1002/jcb.22907
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inflammatory protein‐1α induces osteoclast formation by activation of the MEK/ERK/c‐Fos pathway and inhibition of the p38MAPK/IRF‐3/IFN‐β pathway

Abstract: Multiple myeloma (MM) is a bone disease that affects many individuals. It was recently reported that macrophage inflammatory protein (MIP)-1α is constitutively secreted by MM cells. MIP-1α causes bone destruction through the formation of osteoclasts (OCs). However, the molecular mechanism underlying MIP-1α-induced OC formation is not well understood. In the present study, we attempted to clarify the mechanism whereby MIP-1α induces OC formation in a mouse macrophage-like cell line comprising C7 cells. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…We used C7 cells, which are mouse macrophage-like cells that have the ability to differentiate into osteoclasts [19,20]. The C7 cells were kindly provided by Dr. Shin-ichi Hayashi (Tottori University, Japan) and cultured in α-minimal essential medium (Sigma) supplemented with 10% fetal calf serum (Gibco, Carlsbad, CA), 50 ng/mL human recombinant M-CSF (Leukoprol; Kyowa Hakko, Shizuoka, Japan), 100 U/mL penicillin (Gibco) and 100 μg/mL streptomycin (Gibco), in an atmosphere containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…We used C7 cells, which are mouse macrophage-like cells that have the ability to differentiate into osteoclasts [19,20]. The C7 cells were kindly provided by Dr. Shin-ichi Hayashi (Tottori University, Japan) and cultured in α-minimal essential medium (Sigma) supplemented with 10% fetal calf serum (Gibco, Carlsbad, CA), 50 ng/mL human recombinant M-CSF (Leukoprol; Kyowa Hakko, Shizuoka, Japan), 100 U/mL penicillin (Gibco) and 100 μg/mL streptomycin (Gibco), in an atmosphere containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was reported that MIP1␣ (macrophage inflammatory protein 1␣) induces osteoclast formation by activating the MEK/ERK/c-Fos pathway (26) and that vitamin E inhibits RANKL-induced osteoclast differentiation from precursors by suppression of c-Fos expression, possibly through inhibiting ERK (27). To investigate the role of the ERK, JNK, and p38 pathways in the inhibitory effect of NMP, RAW264.7 cells were treated as indicated in Fig.…”
Section: Nmp Inhibits Nfatc1 and C-fos Expression And Decreases Ap-1 mentioning
confidence: 99%
“…MIP‐1α promotes cell growth and survival by binding to chemokine receptor 1 (CCR1) and CCR5, and activating ERK1/2 and Akt (Lentzsch et al, ; Tsubaki et al, , ). In the present study, we investigated the mechanism of enhanced cytotoxicity of melphalan with MIP‐1α neutralizing antibody.…”
Section: Discussionmentioning
confidence: 99%